2019
DOI: 10.24820/ark.5550190.p010.934
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly-functionalized pyrazoles under Vilsmeier-Haack reaction conditions

Abstract: Synthesis of 1,3-disubstituted 5-chloro-1H-pyrazole-4-carbaldehydes was achieved by formylation of the corresponding 5-chloro-1H-pyrazoles under Vilsmeier-Haack conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 31 publications
(54 reference statements)
0
28
0
Order By: Relevance
“…The 35 Cl NQR spectral data of a polycrystalline sample of 3,5-dichloro-l,2,4-triazole (1) differs insignificantly in the signal intensity ratios from those reported previously (Table 1) [70]. The 35 Cl NQR spectrum of 1 also differs from that expected from the single crystal X-Ray analysis (ambient temperature) [71]. These data assume that compound 1 could be a 1-H tautomer (A).…”
Section: Chlorinated Five-membered Azolesmentioning
confidence: 72%
See 4 more Smart Citations
“…The 35 Cl NQR spectral data of a polycrystalline sample of 3,5-dichloro-l,2,4-triazole (1) differs insignificantly in the signal intensity ratios from those reported previously (Table 1) [70]. The 35 Cl NQR spectrum of 1 also differs from that expected from the single crystal X-Ray analysis (ambient temperature) [71]. These data assume that compound 1 could be a 1-H tautomer (A).…”
Section: Chlorinated Five-membered Azolesmentioning
confidence: 72%
“…We studied the 3,5-dichloro-1,2,4-triazole (1) by 35 Cl NQR spectroscopy and showed that it also exists as the 1H-tautomer (Scheme 2) (Table 1) [46,68,69]. The 35 Cl NQR spectral data of a polycrystalline sample of 3,5-dichloro-l,2,4-triazole (1) differs insignificantly in the signal intensity ratios from those reported previously (Table 1) [70]. The 35 Cl NQR spectrum of 1 also differs from that expected from the single crystal X-Ray analysis (ambient temperature) [71].…”
Section: Chlorinated Five-membered Azolesmentioning
confidence: 99%
See 3 more Smart Citations